Needle-like aggregate ZSM-5 molecular sieve as well as preparation method and application thereof

By melting metakaolin with alkaline substances and subjecting hydrothermal crystallization with other raw materials, a needle-shaped agglomerated ZSM-5 molecular sieve was prepared, which solved the problem of limitations in the use of aluminum sources in the prior art and achieved efficient catalytic effect of light hydrocarbon cracking.

CN119612543APending Publication Date: 2025-03-14SHANDONG CHAMBROAD PETROCHEMICALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411868200.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

In the prior art, when preparing ZSM-5 molecular sieve by hydrothermal method, the aluminum source is mainly aluminum hydroxide or sodium metaaluminate, and metakaolin is rarely used as the aluminum source, resulting in limitations in the preparation method.

Method used

Metakaolin is mixed with alkaline substances and melted, metakaolin is activated, then mixed with silicon source, template agent and solvent, and hydrothermal crystallization is carried out. Finally, needle-shaped agglomerate ZSM-5 molecular sieve is prepared by ion exchange and calcination.

Benefits of technology

Through this method, the prepared needle-shaped agglomerate ZSM-5 molecular sieve has a large specific surface area and pore volume, which is suitable for light hydrocarbon cracking catalysts, improving the reaction conversion rate and diene selectivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention provides a needle-like aggregate ZSM-5 molecular sieve as well as a preparation method and application thereof. According to the preparation method, metakaolin is used as an aluminum source and is mixed and melted with an alkaline substance, so that metakaolin is softened, and subsequent mixing with substances such as a silicon source is facilitated. According to the preparation method, metakaolin is taken as an aluminum source, an obtained molten product is mixed with a silicon source, a template agent and a solvent, and then hydrothermal crystallization treatment is carried out, so that the molecular sieve grows into a special morphology of needle-like aggregates, single crystal grains of the needle-like aggregates are small, intergranular mesopores exist among the aggregates, and the molecular sieve has a high molecular weight. The total specific surface area, the micropore specific surface area, the mesopore specific surface area, the mesopore volume and the micropore volume of the synthesized ZSM-5 molecular sieve are favorably improved. The needle-like aggregate ZSM-5 molecular sieve is used as an active component of a light hydrocarbon cracking catalyst and is used for light hydrocarbon cracking, and the diene selectivity can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of molecular sieves, and in particular relates to a needle-shaped aggregate ZSM-5 molecular sieve and a preparation method and application thereof. Background Art

[0002] Metakaolin (Al 2 O 3 ·2SiO 2 ·2H 2 O) is made of kaolin with a silicon-aluminum ratio of 1 (Al 2 O 3 ·2SiO 2 ·2H 2 O) The product after calcination has the advantages of low cost and high natural abundance, and is a raw material for synthesizing molecular sieves. At present, there are several synthetic methods for producing molecular sieves using natural raw materials (kaolin and metakaolin). For example, type A molecular sieves are synthesized using metakaolin as a raw material and microwave-assisted heating.

[0003] At present, the method of preparing ZSM-5 molecular sieve by hydrothermal method is more common, but the aluminum sources used are mostly aluminum hydroxide, sodium aluminate and other substances, and there are few literature studies on using kaolin as an aluminum source. Summary of the invention

[0004] In view of this, the object of the present invention is to provide a needle-shaped aggregate ZSM-5 molecular sieve and a preparation method and application thereof. The needle-shaped aggregate ZSM-5 molecular sieve has a special pore structure and has good application prospects in light hydrocarbon cracking reactions.

[0005] To achieve this object, the present invention adopts the following technical solutions:

[0006] In a first aspect, the present invention provides a method for preparing a needle-shaped aggregate ZSM-5 molecular sieve, comprising the following steps:

[0007] S1: Mixing and melting metakaolin and alkaline substances to obtain a molten product;

[0008] S2: mixing the molten product, silicon source, template and solvent, and performing hydrothermal crystallization treatment to obtain a molecular sieve solid;

[0009] S3: placing the molecular sieve solid in an ammonium salt solution for ion exchange and calcining to obtain a needle-shaped aggregate molecular sieve.

[0010] Preferably, the molten product is ball-milled and then mixed with a silicon source, a template and water.

[0011] Preferably, the ball milling treatment time is 1 to 8 h.

[0012] Preferably, the alkaline substance is selected from organic bases and / or inorganic bases.

[0013] Preferably, the silicon source is selected from any one or more of tetraethyl orthosilicate, silica sol or silica gel.

[0014] Preferably, the template agent is selected from any one or more of tetrapropylammonium hydroxide, n-butylamine or tetrapropylammonium bromide.

[0015] Preferably, the solvent is selected from water.

[0016] The ammonium salt is selected from any one or more of ammonium nitrate, ammonium chloride or ammonium acetate.

[0017] Preferably, the SiO in the silicon source 2 Calculated, Al in metakaolin 2 O 3 The molar ratio of the metakaolin, silicon source, template, solvent and alkaline substance is (0.01~0.033):1:(0.2~0.8):(13~33):(0.1~0.3).

[0018] Preferably, the concentration of the ammonium salt solution is 0.05~0.6 M, and the mass ratio of the molecular sieve solid to the ammonium salt solution is (0.05~0.2):1.

[0019] Preferably, the melting temperature is 600-800° C. and the melting time is 0.5-3 h.

[0020] Preferably, the temperature of the hydrothermal crystallization treatment is 160-200° C., and the time is 36-96 h.

[0021] Preferably, the calcination temperature is 550-650° C. and the calcination time is 3-5 h.

[0022] Preferably, the specific surface area of ​​the needle-shaped aggregate ZSM-5 molecular sieve is 525 m 2 / g or more, micropore specific surface area is 420 m 2 / g or more, and the mesopore specific surface area is 65 m 2 / g or more, and the micropore volume is 0.20 cm 3 / g or more, and the mesopore volume is 0.10 cm 3 / g or above.

[0023] In a second aspect, the present invention provides a light hydrocarbon cracking catalyst, wherein the needle-shaped agglomerate ZSM-5 molecular sieve prepared by the above preparation method is used as an active component.

[0024] In a third aspect, the present invention provides an application of the above-mentioned light hydrocarbon cracking catalyst in light hydrocarbon cracking.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] The present invention provides a method for preparing a needle-shaped agglomerate ZSM-5 molecular sieve, wherein the preparation method uses metakaolin as an aluminum source, and mixes and melts with an alkaline substance, thereby activating the metakaolin and facilitating subsequent mixing with a silicon source and other substances. In the present invention, metakaolin is used as an aluminum source, and the obtained molten product is mixed with a silicon source, a template agent and a solvent, and then subjected to a hydrothermal crystallization treatment, so that the molecular sieve grows into a special morphology of needle-shaped agglomerates, wherein the single crystal grains of the needle-shaped agglomerates are small, and there are intercrystalline mesopores between the agglomerates, which is beneficial to improving the total specific surface area, micropore specific surface area, mesopore specific surface area, mesopore pore volume and micropore pore volume of the synthesized ZSM-5 molecular sieve.

[0027] The needle-shaped aggregate ZSM-5 molecular sieve obtained by the preparation method is used as the active component of the light hydrocarbon cracking catalyst for light hydrocarbon cracking. With the help of the large specific surface area and pore volume of the molecular sieve, it is beneficial for the macromolecular reaction substrate to enter the pore structure of the molecular sieve and contact with the B acid site, thereby improving the reaction conversion rate. In addition, the large specific surface area and pore volume are beneficial for the diffusion of product molecules and leaving the acid center, thereby improving the diene selectivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 The XRD spectra of the samples obtained in Example 1 and Comparative Examples 1-2 are shown in FIG.

[0029] Figure 2 The following are SEM images of the samples obtained in Example 1 and Comparative Example 2. DETAILED DESCRIPTION

[0030] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] The present invention provides a method for preparing a needle-shaped aggregate ZSM-5 molecular sieve, comprising the following steps:

[0032] S1: Mixing and melting metakaolin and alkaline substances to obtain a molten product;

[0033] S2: mixing the molten product, silicon source, template and solvent, and performing hydrothermal crystallization treatment to obtain a molecular sieve solid;

[0034] S3: Mixing the ammonium salt with the molecular sieve solid and performing ion exchange and calcination to obtain a needle-shaped agglomerate molecular sieve.

[0035] In the present invention, the metakaolin (Al 2 O 3 ·2SiO 2 ·2H 2 O) is used as an aluminum source, which can be a common commercially available material without further treatment.

[0036] In the present invention, the alkaline substance is used for melting of metakaolin on the one hand, and for providing an alkaline environment required for the subsequent synthesis of ZSM-5 molecular sieve on the other hand. The alkaline substance is selected from organic bases and / or inorganic bases, and specifically can be selected from one or more of sodium hydroxide, potassium hydroxide, calcium hydroxide or tetrapropylammonium hydroxide.

[0037] According to the present invention, firstly, metakaolin and alkaline substances are mixed and melted to obtain a molten product. The melting temperature is 600-800°C, preferably 650-750°C; the time is 0.5-3 h, preferably 1-2 h. In the present invention, the purpose of the mixed melting is to activate the metakaolin and make it more reactive.

[0038] In the present invention, after obtaining the molten product, the molten product is preferably subjected to ball milling to obtain ground powder, which is conducive to improving its dispersibility when subsequently mixed with a silicon source, a template and water. The ball milling time is 1 to 8 hours, preferably 2 to 5 hours.

[0039] According to the present invention, the molten product (or ground powder), silicon source, template and solvent are preferably mixed and subjected to hydrothermal crystallization treatment to obtain a molecular sieve solid.

[0040] In the present invention, the silicon source is selected from any one or more of tetraethyl orthosilicate, silica sol or silica gel.

[0041] In the present invention, the template agent is selected from any one or more of tetrapropylammonium hydroxide, n-butylamine or tetrapropylammonium bromide.

[0042] In the present invention, the solvent is selected from water, preferably deionized water.

[0043] In the present invention, the above-mentioned metakaolin, alkaline substance, silicon source, template agent and solvent are used as raw materials for preparing molecular sieves. Generally, SiO 2 Calculated, Al in metakaolin 2 O 3The molar ratio of the metakaolin, silicon source, template, solvent and alkaline substance is (0.01-0.033):1:(0.2-0.8):(13-33):(0.1-0.3), preferably (0.01-0.025):1:(0.3-0.6):(15-25):(0.1-0.2). In some embodiments of the present invention, the molten product (or ground powder), silicon source, template and solvent are preferably mixed according to the above ratio, and the hydrothermal crystallization treatment is carried out at 160-200°C for 36-96 h, preferably at 170-180°C for 40-84 h.

[0044] In the present invention, after the hydrothermal crystallization treatment is completed, the metakaolin can be transformed from a flake or layered structure into a needle-like aggregate.

[0045] According to the present invention, the ammonium salt is then preferably mixed with the molecular sieve solid and ion exchanged and calcined to obtain the needle-like agglomerate molecular sieve.

[0046] In the present invention, the ammonium salt is selected from any one or more of ammonium nitrate, ammonium chloride or ammonium acetate, wherein the ammonium ions can be ion exchanged with the metal cations introduced by the alkaline substance in the molecular sieve solid. After the ion exchange is completed, the ammonium ions are converted into hydrogen ions through calcination and exist in the needle-shaped aggregate molecular sieve.

[0047] In the present invention, the concentration of the ammonium salt solution is 0.05-0.6 M, preferably 0.1-0.6 M; the mass ratio of the molecular sieve to the solution is (0.05-0.2):1, preferably (0.1-0.2):1.

[0048] In the present invention, the calcination temperature is 550-650° C., preferably 580-600° C., and the calcination time is 3-5 h, preferably 3.5-4.5 h.

[0049] The preparation method provided by the present invention is simple and convenient, and can be easily industrialized or industrialized.

[0050] The needle-shaped aggregated ZSM-5 molecular sieve prepared by the preparation method of the present invention has a specific surface area of ​​525 m 2 / g or more, micropore specific surface area is 420 m 2 / g or more, and the mesopore specific surface area is 65 m 2 / g or more, and the micropore volume is 0.20 cm 3 / g or more, and the mesopore volume is 0.10 cm 3 / g or above.

[0051] It can be seen that the needle-shaped agglomerate ZSM-5 molecular sieve obtained by the above preparation method of the present invention has an excellent pore structure. Using it as an active component of a light hydrocarbon cracking reaction catalyst can improve the accessibility of the catalyst's acidic sites, which is beneficial to improving the adsorption and desorption of reactants and products at the active sites, thereby improving the reaction conversion rate, reducing secondary reactions, improving diene selectivity, and reducing coke formation, which is very beneficial to the light hydrocarbon cracking reaction to produce more dienes.

[0052] Based on this, the present invention also provides a light hydrocarbon cracking catalyst, wherein the needle-shaped agglomerate ZSM-5 molecular sieve prepared by the above preparation method is used as an active component.

[0053] The present invention also provides an application of the light hydrocarbon cracking catalyst in light hydrocarbon cracking.

[0054] According to tests, the light hydrocarbon cracking catalyst is used for light hydrocarbon cracking, with a diene yield of more than 30% and a coke generation rate of less than 2.5%.

[0055] In order to further illustrate the present invention, the following examples are provided for detailed description. The experimental raw materials used in the following examples of the present invention are all common commercially available products.

[0056] Example 1

[0057] (1) 0.033 mol of metakaolin and 0.3 mol of sodium hydroxide were mixed and melted at 600 °C for 3 h to obtain solid A;

[0058] (2) Solid A was ball-milled for 3 h to obtain ground powder;

[0059] (3) Add all the ground powder, 1 mol of ethyl orthosilicate, and 0.8 mol of tetrapropylammonium hydroxide to 33 mol of deionized water, mix and stir evenly to obtain gel B;

[0060] (4) Transfer gel B to a reactor and crystallize at 160 °C for 96 h;

[0061] (5) The crystallized molecular sieve was washed with deionized water until neutral, dried at 60°C for 12 h, and calcined at 550°C for 5 h to obtain solid a;

[0062] (6) using an ammonium nitrate solution with a concentration of 0.1 mol / L at a solid-liquid ratio of 1:10 to perform ion exchange on solid a, and then calcining at 550 °C for 5 h to obtain solid b;

[0063] (7) Taking solid b as the active component of the catalyst, 600 g of kaolin, 130 g of aluminum sol, 70 g of phosphoric acid, 400 g of molecular sieve, and 130 g of silica sol are added in the order of mixing and stirring to form a slurry, the slurry is ball-milled, and then spray-formed in a spray dryer;

[0064] (8) The prepared microspheres were calcined at 500 °C for 2 h, and the obtained samples were evaluated using a fixed fluidized bed reactor.

[0065] Example 2

[0066] (1) 0.02 mol of kaolin and 0.2 mol of alkaline substance were mixed and melted at 700 °C for 1 h to obtain solid A;

[0067] (2) Solid A was ball-milled for 1 h to obtain ground powder;

[0068] (3) Add all the ground powder, 1 mol of ethyl orthosilicate, and 0.4 mol of tetrapropylammonium hydroxide to 18 mol of deionized water, mix and stir evenly to obtain gel B;

[0069] (4) Transfer gel B to a reactor and crystallize at 180 °C for 72 h;

[0070] (5) The crystallized molecular sieve was washed with deionized water until neutral, dried at 100°C for 4 h, and calcined at 600°C for 4 h to obtain solid a;

[0071] (6) using an ammonium nitrate solution with a concentration of 0.1 mol / L at a solid-liquid ratio of 1:20 to perform ion exchange on solid a, and then calcining at 600 °C for 4 h to obtain solid b;

[0072] (7) Taking solid b as the active component of the catalyst, 600 g of kaolin, 130 g of aluminum sol, 70 g of phosphoric acid, 400 g of molecular sieve, and 130 g of silica sol are added in the order of mixing and stirring to form a slurry, the slurry is ball-milled, and then spray-formed in a spray dryer;

[0073] (8) The prepared microspheres were calcined at 500 °C for 2 h, and the obtained samples were evaluated using a fixed fluidized bed reactor.

[0074] Example 3

[0075] (1) 0.01 mol of metakaolin and 0.1 mol of sodium hydroxide were mixed and melted at 800°C for 0.5 h to obtain solid A;

[0076] (2) Solid A was ball-milled for 0.5 h to obtain ground powder;

[0077] (3) Add all the ground powder, 1 mol of ethyl orthosilicate, and 0.2 mol of tetrapropylammonium hydroxide to 13 mol of deionized water, mix and stir evenly to obtain gel B;

[0078] (4) Transfer gel B to a reactor and crystallize at 160 °C for 96 h;

[0079] (5) The crystallized molecular sieve was washed with deionized water until neutral, dried at 110°C for 6 h, and calcined at 650°C for 3 h to obtain solid a;

[0080] (6) using an ammonium nitrate solution with a concentration of 0.1 mol / L at a solid-liquid ratio of 1:30, ion exchange was performed on solid a, and then calcined at 650 °C for 3 h to obtain solid b;

[0081] (7) Taking solid b as the active component of the catalyst, 600 g of kaolin, 130 g of aluminum sol, 70 g of phosphoric acid, 400 g of molecular sieve, and 130 g of silica sol are added in the order of mixing and stirring to form a slurry, the slurry is ball-milled, and then spray-formed in a spray dryer;

[0082] (8) The prepared microspheres were calcined at 500 °C for 2 h, and the obtained samples were evaluated using a fixed fluidized bed reactor.

[0083] Example 4

[0084] (1) 0.033 mol of metakaolin and 0.3 mol of potassium hydroxide were mixed and melted at 600 °C for 3 h to obtain solid A;

[0085] (2) Solid A was ball-milled for 3 h to obtain ground powder;

[0086] (3) Add all the ground powder, 1 mol of silica gel, and 0.8 mol of tetrapropylammonium bromide to 33 mol of deionized water, mix and stir evenly to obtain gel B;

[0087] (4) Transfer gel B to a reactor and crystallize at 160 °C for 96 h;

[0088] (5) The crystallized molecular sieve was washed with deionized water until neutral, dried at 60°C for 12 h, and calcined at 550°C for 5 h to obtain solid a;

[0089] (6) using an ammonium chloride solution with a concentration of 0.1 mol / L at a solid-liquid ratio of 1:10 to perform ion exchange on solid a, and then calcining at 550 °C for 5 h to obtain solid b;

[0090] (7) Taking solid b as the active component of the catalyst, 600 g of kaolin, 130 g of aluminum sol, 70 g of phosphoric acid, 400 g of molecular sieve, and 130 g of silica sol are added in the order of mixing and stirring to form a slurry, the slurry is ball-milled, and then spray-formed in a spray dryer;

[0091] (8) The prepared microspheres were calcined at 500 °C for 2 h, and the obtained samples were evaluated using a fixed fluidized bed reactor.

[0092] Example 5

[0093] (1) 0.033 mol of metakaolin and 0.3 mol of tetrapropylammonium hydroxide were mixed and melted at 600 °C for 3 h to obtain solid A;

[0094] (2) Solid A was ball-milled for 3 h to obtain ground powder;

[0095] (3) Add all the ground powder, 4 mol of silica sol (40%), and 0.8 mol of n-butylamine to 33 mol of deionized water, mix and stir evenly to obtain gel B;

[0096] (4) Transfer gel B to a reactor and crystallize at 160 °C for 96 h;

[0097] (5) The crystallized molecular sieve was washed with deionized water until neutral, dried at 60°C for 12 h, and calcined at 550°C for 5 h to obtain solid a;

[0098] (6) using a 0.1 mol / L ammonium acetate solution at a solid-liquid ratio of 1:10 to perform ion exchange on solid a, and then calcining at 550 °C for 5 h to obtain solid b;

[0099] (7) Taking solid b as the active component of the catalyst, 600 g of kaolin, 130 g of aluminum sol, 70 g of phosphoric acid, 400 g of molecular sieve, and 130 g of silica sol are added in the order of mixing and stirring to form a slurry, the slurry is ball-milled, and then spray-formed in a spray dryer;

[0100] (8) The prepared microspheres were calcined at 500 °C for 2 h, and the obtained samples were evaluated using a fixed fluidized bed reactor.

[0101] Comparative Example 1

[0102] (1) Add 0.033 mol of metakaolin, 0.3 mol of sodium hydroxide, 1 mol of ethyl orthosilicate, and 0.8 mol of tetrapropylammonium hydroxide to 33 mol of deionized water, mix and stir evenly to obtain gel A;

[0103] (2) Transfer gel A to a reactor and crystallize at 160 °C for 96 h;

[0104] (5) The crystallized molecular sieve was washed with deionized water until neutral, dried at 60°C for 12 h, and calcined at 550°C for 5 h to obtain solid a;

[0105] (6) using an ammonium nitrate solution with a concentration of 0.1 mol / L at a solid-liquid ratio of 1:10 to perform ion exchange on solid a, and then calcining at 550 °C for 5 h to obtain solid b;

[0106] (7) Taking solid b as the active component of the catalyst, 600 g of kaolin, 130 g of aluminum sol, 70 g of phosphoric acid, 400 g of molecular sieve, and 130 g of silica sol are added in the order of mixing and stirring to form a slurry, the slurry is ball-milled, and then spray-formed in a spray dryer;

[0107] (8) The prepared microspheres were calcined at 500 °C for 2 h, and the obtained samples were evaluated using a fixed fluidized bed reactor.

[0108] Comparative Example 2

[0109] (1) Add 0.033 mol of sodium aluminate, 0.3 mol of sodium hydroxide, 1.033 mol of ethyl orthosilicate, and 0.8 mol of tetrapropylammonium hydroxide to 33 mol of deionized water, mix and stir evenly to obtain gel A;

[0110] (2) Transfer gel A to a reactor and crystallize at 160 °C for 96 h;

[0111] (5) The crystallized molecular sieve was washed with deionized water until neutral, dried at 60°C for 12 h, and calcined at 550°C for 5 h to obtain solid a;

[0112] (6) using an ammonium nitrate solution with a concentration of 0.1 mol / L at a solid-liquid ratio of 1:10 to perform ion exchange on solid a, and then calcining at 550 °C for 5 h to obtain solid b;

[0113] (7) With solid b as the active component of the catalyst, 600 g of kaolin, 130 g of aluminum sol, 70 g of phosphoric acid, 400 g of molecular sieve and 130 g of silica sol are added in the order of mixing and stirring to form a slurry. The slurry is ball-milled and then spray-formed in a spray dryer.

[0114] (8) The prepared microspheres were calcined at 500 °C for 2 h, and the obtained samples were evaluated using a fixed fluidized bed reactor.

[0115] XRD characterization

[0116] XRD characterization was performed on the samples obtained in Example 1 and Comparative Examples 1-2. The results are as follows: Figure 1 As shown. It can be seen that Comparative Example 1 prepared without melt treatment of metakaolin and alkaline substances, Comparative Example 2 prepared without metakaolin as raw material, and Example 1 using metakaolin as raw material and melt treatment all contain MFI phase characteristic diffraction peaks. Among them, Comparative Example 2 and Example 1 have and only have MFI characteristic diffraction peaks, which can prove that both are ZSM-5 pure phase molecular sieves. However, Comparative Example 1 contains a large amount of amorphous, which leads to obvious broadening of diffraction peaks in the XRD spectrum. This proves that pure phase ZSM-5 molecular sieves cannot be prepared using metakaolin as raw material without melt treatment with alkaline substances. Therefore, the present invention no longer performs subsequent characterization and testing on Comparative Example 1.

[0117] SEM characterization

[0118] The samples obtained in Example 1 and Comparative Example 2 were characterized by SEM. Figure 2 shown.

[0119] By comparing the SEM images of Comparative Example 2 and Example 1, it can be seen that the ZSM-5 molecular sieve prepared with tetraethyl orthosilicate and sodium aluminate as raw materials presents a plate-like morphology, and the crystals are dense and flat. However, the ZSM-5 molecular sieve prepared with metakaolin and tetraethyl orthosilicate as raw materials presents a needle-like agglomerate morphology, and there are a large number of intercrystalline stacked mesopores.

[0120] Molecular sieve surface area and pore volume test

[0121] The test method is as follows:

[0122] The synthesized ZSM-5 molecular sieve was analyzed using the Quadrasorb evoTM fully automatic specific surface area and porosity analyzer produced by Quantachrome Company of the United States and the GB / T 21650.2-2008 method.

[0123] The test results are shown in Table 1:

[0124] Table 1 Molecular sieve surface area and pore volume test results

[0125]

[0126] As can be seen from Table 1, the specific surface area of ​​the needle-shaped agglomerate ZSM-5 molecular sieve prepared in Examples 1-5 is significantly higher than that of the plate-shaped ZSM-5 molecular sieve prepared in Comparative Example 2, which is conducive to the rapid contact of the reaction substrate with the acidic site and the rapid separation of the product, thereby improving the reaction conversion rate and reducing secondary reactions.

[0127] Fixed fluidized bed reactor evaluation test experiment

[0128] The test method is as follows:

[0129] The above embodiments and comparative examples of molecular sieve catalysts were applied to the cracking reaction of gasoline. The reaction temperature was 650 o C, the flow rates of naphtha and nitrogen were 3 mL / min and 300 mL / min, respectively, the flow rate of fluidizing steam was 8 mL / min, and 200 g of catalyst was loaded into the reactor for catalytic cracking performance evaluation.

[0130] Among them, the physical properties of the raw oil involved are shown in Table 2:

[0131] Table 2 Physical properties of crude oil

[0132]

[0133] The test results are shown in Table 3 below:

[0134] Table 3 Physical properties and catalytic performance of samples in the examples

[0135]

[0136] As can be seen from Table 3, the diene yields of Examples 1-5 are all higher than those of Comparative Example 2. This is because the molecular sieves with needle-like agglomerate morphology are loosely stacked, and there are a large number of intercrystalline stacked mesopores in the crystals, which increases the specific surface area, mesopore surface area and mesopore volume of the molecular sieve. The diffusion rate of the reaction substrate and product molecules on the needle-like agglomerate molecular sieve is accelerated, which improves the conversion rate of the reaction, reduces the secondary reaction of the product molecules, reduces the generation of dry gas and coke, and improves the diene selectivity.

[0137] In addition, in Examples 1-3, as the amount of metakaolin (providing all aluminum sources and part of the silicon source) introduced decreases, the silicon-aluminum ratio of the prepared molecular sieve gradually increases, reducing the number of acid sites of the molecular sieve, resulting in a decrease in the reaction conversion rate, and a slight decrease in the diene selectivity, but still higher than the diene selectivity of Comparative Example 2. By comparing Example 1, Example 4 and Example 5 with the same amount of silicon source and aluminum source introduced, it can be seen that changing the silicon source has little effect on the performance of the prepared molecular sieve.

[0138] The above description of the disclosed embodiments enables those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing needle-shaped aggregated ZSM-5 molecular sieve, characterized in that: The following steps are involved: S1: Mixing and melting metakaolin and alkaline substances to obtain a molten product; S2: mixing the molten product, silicon source, template and solvent, and performing hydrothermal crystallization treatment to obtain a molecular sieve solid; S3: placing the molecular sieve solid in an ammonium salt solution for ion exchange and calcining to obtain a needle-shaped aggregate molecular sieve.

2. The preparation method according to claim 1, characterized in that: The molten product is ball-milled and then mixed with a silicon source, a template and water; The ball milling treatment time is 1 to 8 h.

3. The preparation method according to claim 1 or 2, characterized in that: The alkaline substance is selected from organic bases and / or inorganic bases; The silicon source is selected from any one or more of tetraethyl orthosilicate, silica sol or silica gel; The template agent is selected from any one or more of tetrapropylammonium hydroxide, n-butylamine or tetrapropylammonium bromide; The solvent is selected from water; The ammonium salt is selected from any one or more of ammonium nitrate, ammonium chloride or ammonium acetate.

4. The preparation method according to any one of claims 1 to 3, characterized in that Based on SiO2 in the silicon source and Al2O3 in the metakaolin, the molar ratio of the metakaolin, the silicon source, the template, the solvent and the alkaline substance is (0.01-0.033):1:(0.2-0.8):(13-33):(0.1-0.3); The concentration of the ammonium salt solution is 0.05-0.6 M, and the mass ratio of the molecular sieve solid to the ammonium salt solution is (0.05-0.2):

1.

5. The preparation method according to any one of claims 1 to 4, characterized in that The melting temperature is 600-800°C and the melting time is 0.5-3 h.

6. The preparation method according to any one of claims 1 to 5, characterized in that The temperature of the hydrothermal crystallization treatment is 160-200° C., and the time is 36-96 h.

7. The preparation method according to any one of claims 1 to 6, characterized in that The calcination temperature is 550-650° C. and the calcination time is 3-5 h.

8. The needle-shaped aggregate ZSM-5 molecular sieve prepared by the preparation method according to any one of claims 1 to 7, characterized in that: Its specific surface area is 525 m 2 / g or more, micropore specific surface area is 420 m 2 / g or more, mesopore specific surface area is 65m 2 / g or more, and the micropore volume is 0.20 cm 3 / g or more, and the mesopore volume is 0.10 cm 3 / g or above.

9. A light hydrocarbon cracking catalyst, characterized in that: The needle-shaped aggregated ZSM-5 molecular sieve prepared by the preparation method described in any one of claims 1 to 7 is the active component.

10. Use of the light hydrocarbon cracking catalyst according to claim 9 in light hydrocarbon cracking.